Unravelling the practical solar charging performance limits of redox flow batteries based on a single photon device system. Issue 9 (15th July 2019) - Bae, Dowon; Faasse, Gerrit M.; Kanellos, Gerasimos; Smith, Wilson A.
Abstract : We present the theoretical model reflecting experimental parameters, such that we can highlight critical parameters that merit the most attention in further studies towards the practical realisation of solar-rechargeable redox flow batteries (SRFBs). Abstract : In recent years, solar redox flow batteries have attracted attention as a possible integrated technology for simultaneous conversion and storage of solar energy. Unlike solar water splitting technologies which require at least 1.8 V for meaningful performance, a lesson learned from previous studies on solar redox flow batteries (SRFBs) is that even single-photon devices can demonstrate unbiased photo-charging owing to the flexibility of redox couple selection. Thus, in this paper, we present a theoretical model reflecting experimental parameters, such that we can highlight important parameters that merit the most attention in further studies towards the practical development of SRFBs. Importantly, the results clearly show how to choose an optimum combination of semiconductors and redox couples under unavoidable conditions that a practical system would encounter, including, but not limited to, optical loss by the electrolyte, overpotential, device architecture and chemical potentials.